A novel ubiquitin-protein ligase E3 functions as a modulator of immune response against lipopolysaccharide in Pacific oyster, Crassostrea gigas. (July 2016) - Cheng, Qi; Wang, Hao; Jiang, Shuai; Wang, Lingling; Xin, Lusheng; Liu, Conghui; Jia, Zhihao; Song, Linsheng; Zhu, Beiwei
Abstract: Ubiquitination is an important post-translational protein modification and plays a crucial role in various processes such as cell cycle, signal transduction, and transcriptional regulation. In the present study, a novel ubiquitin (Ub)-protein ligase E3 (designed as Cg E3Rv1) was identified from Crassostrea gigas, and its ubiquitination regulation in the immune response against lipopolysaccharide (LPS) stimulation was investigated. The open reading frame of Cg E3Rv1 gene was of 1455 bp encoding a polypeptide of 484 amino acids with the predicted molecular mass of 54.89 kDa. There were two transmembrane regions and a RING-variant (RINGv) domain identified in Cg E3Rv1. Cg E3Rv1 shared similar C4HC3 zinc-finger-like motif with those RINGv domain Ub-protein ligases E3s identified from vertebrates and invertebrates, and it was closely clustered with the membrane-associated RING-CH2 (MARCH2) Ub-protein ligases E3s in the phylogenetic tree. The mRNA transcript of Cg E3Rv1 was highest expressed in gonads and hemolymph ( p  < 0.05), and its mRNA expression level in hemocytes was significantly increased at 6 h ( p  < 0.01) after the stimulation of LPS, while the up-regulated mRNA expression was significantly decreased ( p  < 0.01) after acetylcholine stimulation. No significant changes of Cg E3Rv1 expression were observed after peptidoglycan or mannan stimulation. Immunohistochemistry and in situ hybridization assays revealed that Cg E3Rv1 protein and mRNA were dominantly distributed in the gonad. In the hemocytes, Cg E3Rv1 was mainly located around the nucleus, and slightly distributed in the cytoplasm and on the cell membrane. Recombinant Cg E3Rv1 RINGv domain protein (r Cg E3Rv1-RINGv) was confirmed to activate the Ub reaction system in vitro with the aid of Ub-activating enzyme E1 and Ub-conjugating enzyme E2. These results demonstrated that Cg E3Rv1 was an Ub-protein ligase E3, which was involved in the immune response against LPS and the interaction with cell surface signal molecules of neuroendocrine-immune system in oysters. Highlights: A ubiquitin-protein ligase E3 ( Cg E3Rv1) was identified from Crassostrea gigas . The expression of Cg E3Rv1 mRNA was highest in gonads and hemolymphs. Its mRNA was up-regulated post LPS stimulation while decreased after ACh stimulation. r Cg E3Rv1-RINGv could induce the ubiquitination in vitro as a typical Ub-protein ligase E3. Cg E3Rv1 plays an important role in immune defense in C. gigas .